Eco School Berbasis Gamifikasi Untuk meningkatkan Kepedulian terhadap Lingkungan - Andi Muawiyah; Sry Astuti Ningsih; Farida Febrianti (PT Pustaka Cendekia Publisher, 2025)
This community service program aims to foster elementary school students' environmental awareness through a fun and participatory gamification approach. The activities were carried out over three weeks in Grade 3 Anas bin Malik at SDIT Buahati Islamic School Mamuju. The program, titled Eco School, engaged students in completing daily challenges related to environmentally friendly behavior, such as bringing their own water bottles and lunch boxes, maintaining classroom cleanliness by properly disposing of waste and avoiding storing trash in desk drawers, and taking care of plants. Students earned points for each successfully completed challenge, and those who consistently performed well and achieved the highest scores were rewarded as the best students in the class. The results of the program showed a noticeable improvement in students’ awareness and behavior regarding cleanliness and environmental care. This program has proven to be an effective educational strategy—simple yet impactful.